Insurance company investment : principles and policy - Clayton, George; Osborn, William Thompson (London : George Allen & Unwin Ltd., 1965)
It is the authors' intention to examine the nature of the savings which the insurance companies administer and their relative importance as compared with other sources of savings. The next task is to develop the theory of portfolio choice as applied to insurance companies and to determine how they may be expected to behave in achieving their various investment objectives. Then, putting into consideration the impact of the insurance companies' investment behavior on monetary theory, Government policy and the capital market as a whole.
Includes index.
Includes bibliographical references: p. [263]-268.
ne 14/05/2018
Loans
Keywords: Insurance companies; Insurance